PETUNJUK PRAKTIS PENCEGAHAN KECELAKAANDALAM PROSES PEMBELAJARAN PENDIDIKANJASMANI DI SEKOLAH MENENGAH PERTAMA DAN ATAS - Yustinus Sukarmin (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
Accidents are not desirable. It makes someone lose their time, their wealth, and it cancause injury, cripple and even death. It can happens anywhere, at anytime, on anyone.Accident can happen on student when the sport lesson held.Sport lesson compared with other lessons, considering the characteristic, are accidentprone.Taking into account the level of physical and technique of junior and senior highschool pupils, the likelihood of the accident increased. To prevent those accident and theeffects afterward, the teacher must identify the sources.Accident in sport lesson can be caused by internal factor (intrinsic), e.g. exhausted, harumscarum,lack of skill and not having adequate pre-game warm-up and stretching. Otherpossibilities are came from outside factors (extrinsic), e.g. poor equipment and facilities,bad weather, terrible location, inadequate referee.Keyword: accident, sport lesson, Junior and senior high school.